G228(P) Comparing children's and parents' perspectives on hospital care. (7th April 2014) - Rodrigues, S; Melchionda, V; Rodney, K; Coppens, K
Abstract : Feedback from patients is essential in order to achieve patient centred care. In the paediatric environment, the need to hear directly from children has been identified since the 1990's, but we are still struggling to hear children's voices in relation to their medical care. Parents' opinions are often obtained, however their views may not necessarily reflect those of their children. There is currently very limited published information on children's opinions of hospital care and how these are reflected by parental feedback. The aims of this quality improvement project are to identify children's priorities and to investigate whether differences exist between parents' and children's perspectives on hospital staff and environment. The overall aim is to introduce and maintain a culture of routinely seeking children's perspectives. Feedback from questionnaires and dissemination of results to staff will allow service improvements to be more closely tailored towards the whole family's needs. We used the expertise of both clinical staff and inpatient school teachers to develop two questionnaires for children aged 6–11 years and 12–18 years, and a corresponding parental questionnaire. These were distributed on an inpatient paediatric ward of a large teaching hospital. Participants were asked to rate their experiences regarding hospital staff and environment, and to answer open questions on how services could be improved. Parental and patient questionnaires were reviewed anonymously. A total of 77 paired patient and parental questionnaires were completed. Ward environment and staff interactions were found to be priorities for both children and parents, whilst children focused more on ward based activities when suggesting improvements. Children gave higher scores than parents for most staff and environment categories. Differences in priorities were also noted between individual patient and parent pairs. Suggestions were used to improve services, for example by provision of headphones to reduce noise levels on the ward and setting up of a student led play service to cover times when play therapists are unavailable. Results of this project confirm that children's views are not always mirrored by their parents. This highlights the need to develop methods of obtaining more direct feedback from children in order to improve patient centred care.